Mobile journalism: the emergence of a new field of journalism - Rodrigues, Luis Pedro Ribeiro (2021)
This article was developed within the scope of the Erasmus+ PAgES project, and it aims to investigate mobile journalism (mojo) as a new digital journalism technique that is based upon three characteristics: agility, flexibility, and accessibility. The proposed hypotheses are that mobile journalists can produce news content quickly and also include a greater variety of formats. In addition, access to remote locations and characters for interviews has been facilitated. Exploratory research tested these hypotheses using a mixed-method approach: an online survey (53 responses), to assess the degree of agreement/disagreement of the mobile journalists themselves regarding the hypotheses; and four interviews with experts to understand their perceptions of this new approach to journalism. The result of the research was favorable to the hypotheses and confirmed the process of individualization in journalism. It also ratified mojo as a journalistic technique suited to the demands of the 21st-century media industry.